1986
DOI: 10.1056/nejm198609183151203
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Chloroquine on Serum 1,25-Dihydroxyvitamin D and Calcium Metabolism in Sarcoidosis

Abstract: Although corticosteroids are effective in the treatment of hypercalciuria and hypercalcemia in chronic sarcoidosis, complications of their long-term use frequently limit therapy. We studied the efficacy of chloroquine in two patients with sarcoidosis who were unable to tolerate the dosage of corticosteroids required to control hypercalciuria and prevent the formation of renal stones. Over a three-year period, each patient received a 6-month and a 10-month course of oral chloroquine phosphate (500 mg per day) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0
2

Year Published

1991
1991
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(54 citation statements)
references
References 22 publications
1
51
0
2
Order By: Relevance
“…Patients with SLE often take hydroxychloroquine, which has been suspected to reduce the conversion of 25(OH)D3 to the more biologically active 1,25(OH)2D3 [27]. Lower 1,25(OH)2D3 levels was reported in patients with lupus treated with hydroxychloroquine, although circulating 25(OH)D3 levels did not differ.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with SLE often take hydroxychloroquine, which has been suspected to reduce the conversion of 25(OH)D3 to the more biologically active 1,25(OH)2D3 [27]. Lower 1,25(OH)2D3 levels was reported in patients with lupus treated with hydroxychloroquine, although circulating 25(OH)D3 levels did not differ.…”
Section: Discussionmentioning
confidence: 99%
“…In several case reports, serum calcium normalized within several weeks to months. (21)(22)(23) In one case, calcium and 1,25(OH) 2 D levels remained normal 18 months after discontinuation of chloroquine. (22) Limited data and the relatively high rate of spontaneous resolution of sarcoidosis make this observation difficult to interpret.…”
Section: Discussionmentioning
confidence: 94%
“…While the exact mechanism by which chloroquine reduces 1,25(OH) 2 D levels is unknown, it may impair granuloma formation. (22,23) Reichel and colleagues showed that chloroquine may induce 24-hydroxylase activity, thereby inactivating both 25(OH)D and 1,25(OH) 2 D. (13) The onset of action of chloroquine is slower than that of corticosteroids, but its effect may be more durable. In several case reports, serum calcium normalized within several weeks to months.…”
Section: Discussionmentioning
confidence: 99%
“…553 Table 38 compares the toxicity of chloroquine to hydroxychloroquine. Table 39 summarizes the 11 reports of using an antimalarial agent for sarcoidosis [554][555][556][557][558][559][560][561][562][563] along with one series of use of these drugs for pulmonary fi brosis. 564 3.7.1.1 Toxicity-Chloroquine toxicity is most frequently encountered when parenteral routes are used to treat comatose patients with malaria.…”
Section: Information For Patientsmentioning
confidence: 99%